Digital Activism and International Relations: The Intersection of the Israel-Palestine Conflict and the McDonald’s and Starbucks Boycott in Europe - Hussin, Mutia Hariati; Makatita, Gamal Abdul Nasir (President University, 2024)
Digital Activism has emerged as a powerful tool in today's global landscape, empowering individuals and groups to express their opinions swiftly and effectively. Digital activism has assumed a prominent role in international relations, particularly in addressing contentious international conflicts. This article delves into the nexus between digital activism and international relations, specifically focusing on the enduring Israel-Palestine conflict. This study examines how digital activism shapes the dynamics of the Israel-Palestine conflict and elucidates the emergence of the boycott movement targeting global brands like McDonald's and Starbucks as a notable expression of this activism. The research uses qualitative methods to analyze data gathered from diverse news sources, including Euronews, BBC, CNBC, inews.uk, the Washington Post, The Guardian, and the BDS Movement. The analysis employs narrative and sentiment analysis techniques facilitated by Qualitative Data Analysis (Q-DAS), specifically NVivo 12 Plus. Findings reveal: First, most news content is dominated by sharing Information and raising the voice. Second, almost all news circulating is connected through the narrative of protesters and Palestinians. Third, the narration is dominated by human rights themes and rejection of the support of fast-food companies. Therefore, this research is expected to contribute to a deeper understanding of the intersection between digital activism and international relations, shedding light on its implications for contemporary global dynamics.Keywords: Digital Activism, Europe, Israel-Palestine Conflict, Boycott, MNC